MORAL EDUCATION IN JAPANESE SCHOOLS A MODEL FOR IMPROVING CHARACTER EDUCATION IN INDONESIA - Junaedi, Mahfud; Syukur, Fatah (Analisa: Journal of Social Science and Religion, 2017)
Moral or character education has been playing an important role in educating children, teenagers, and younger people noble values of Japanese cultures. This research is based on two research questions: how the practice of moral education in Japanese schools is and how the model for improving character education in Indonesian schools is. This is a qualitative field research with phenomenological approach, in which the data were collected in Japanese schools by using observation, indepth interview, and documentary. The data were analysed descriptively and continuously. The Japanese government gave one hour  lesson for moral education in a week.  With the moral education, Japanese younger generation is expected to be able to adapt to the social environment and have the ability to think, to make effective decisions and to act independently. In addition, they are also expected to have  ability to identify issues they face, and be able to interact with others in international relations and play an important role in international world as well. Japanese moral education has been using the interactive and communicative approach, promoting moral discovery by learners themselves, avoiding the application of indoctrination approach, and no test or  final exam,  for every course of study in moral education (zero test).  In addition the most important thing is that moral education in Japan  applied an  integrated and connected approach among  three centers of education: school,  family, and  community.  All of three educational environments have very important role  as laboratory of  moral or character education.